Caring about care-givers: A study of child care workers in Cape Town - S.C. Block (AOSIS, 1985)
Most of the available research on child care has focused on the child, rather than on the person who is providing the care. However, an understanding of the stresses facing the staff person and the ways in which he or she copes with them, is critical for ensuring that that person delivers high-quality care and teaching to the child (Maslach and Pines 1977, 105).